solve 5x+2=ax -1 for x. assume that a is not 0. Describe each step.

*I solved for A on accident last time*

5x+2=ax -1 for x

1. Move the 2 over by subtracting it.

5x+2=ax -1

5x=ax-1-2

5x=ax-3

2. Subtract ax to the other side

5x-ax=-3

2. Undistribute the x

x(5-a)=-3

3. Divide by 5-a

x= -3/ 5-a

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up